2014
DOI: 10.2337/db13-1829
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive In Vivo Imaging of Diabetes-Induced Renal Oxidative Stress and Response to Therapy Using Hyperpolarized 13C Dehydroascorbate Magnetic Resonance

Abstract: Oxidative stress has been proposed to be a unifying cause for diabetic nephropathy and a target for novel therapies. Here we apply a new endogenous reduction-oxidation (redox) sensor, hyperpolarized (HP) 13C dehydroascorbate (DHA), in conjunction with MRI to noninvasively interrogate the renal redox capacity in a mouse diabetes model. The diabetic mice demonstrate an early decrease in renal redox capacity, as shown by the lower in vivo HP 13C DHA reduction to the antioxidant vitamin C (VitC), prior to histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 51 publications
1
64
0
Order By: Relevance
“…Oxidative stress contributes to the pathogenesis of diabetic nephropathy [33] and the KEAP1–NRF2 system even governs antioxidant redox signalling to prevent the initiation of diabetes mellitus [34, 35]. We and others have demonstrated the beneficial role of NRF2 induction in the prevention of diabetic nephropathy [2, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress contributes to the pathogenesis of diabetic nephropathy [33] and the KEAP1–NRF2 system even governs antioxidant redox signalling to prevent the initiation of diabetes mellitus [34, 35]. We and others have demonstrated the beneficial role of NRF2 induction in the prevention of diabetic nephropathy [2, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Dehydroascorbic acid (DHA), the oxidized form of AA, was developed as an investigative probe to measure chemical reduction potential. An increased amount of [1- 13 C] DHA reduction to [1- 13 C] AA in vivo was found to correlate with increased intracellular antioxidant concentrations in a diabetic mouse model [48], indicating HP [1- 13 C] DHA reduction may assess the altered redox capacity in disease and may also hold the potential to monitor treatment response. The long T 1 ’s observed for [1- 13 C] DHA (56 s) are favorable for clinical field strengths but [1- 13 C] DHA still suffers from low overall liquid-state polarization (~6%).…”
Section: Physical and Biological Properties Of Polarized Agentsmentioning
confidence: 99%
“…Using a hyperpolarized [1- 13 C]pyruvate, Laustsen et al has shown that reduction of inspired oxygen increases renal lactate and alanine formation in diabetic mice, while this effect is not observed in non-diabetic controls [41, 42], indicating that reduced oxygen availability alters renal energy metabolism in diabetes. Further, Keshari et al has assessed the oxidative stress in diabetic mouse kidneys using a hyperpolarized [1- 13 C] dehydroascorbate (DHA), a new endogenous redox sensor, and shown that redox capacity is decreased in diabetic kidneys prior to histological evidence of nephropathy and that angiotensin converting enzyme inhibition restores the renal redox status in diabetic mice [43]. Further, Clatworthy et al has assessed renal fumarate metabolism in folic acid-induced AKI mice using this technique and shown that renal production of [1,4- 13 C 2 ]malate, a fumarate metabolite, is increased in early phase of AKI [44].…”
Section: Assessment Of Renal Metabolismmentioning
confidence: 99%